Kajian Lalu Lintas Angkutan Udara Penumpang dan Kargo di Bandara Internasional Soekarno-Hatta - Dina Yuliana (Research and Development Agency of The Ministry of Transportation, 2010)
Forecasting is needed in the planning and designing process structure and infrastructure of airport such as air side facilities, supporting facilities. land side facilities, and even the road network from and to the airport. Airport development is on air traffic forecasting. By using a quantitative model with exponential smoothing and the regression model (causal) will be obtained traffic forecats of air transport passengers and cargo at Soekarno-Hatta Internasional Airport. The results of the study showed that growth prediction of air transport in 2010 for 8.75% and the growth of air cargo decreased by -2.17%